Molecular docking of monkeypox (mpox) virus proteinase with FDA approved lead molecules - M.Valan Arasu; P. Vijayaragavan; Sumitha Purushothaman; M.A. Rathi; Naif Abdullah Al-Dhabi; V.K. Gopalakrishnan; Ki Choon Choi; S. Ilavenil (Elsevier, 2023)
Background: Monkeypox virus (mpox) disease is caused by a double-stranded DNA virus from the Poxviridae family. The mpox virus showed structural similarity with smallpox virus disease. The recent outbreak of mpox infection in the rest of African countries causes public health issues of increased pandemic potential. Mpox virus is involved in the viral replication cycle through the biocatalytic reaction of precursor polyproteins cleavage. Objectives: The main objective of the study was to analyze the molecular interactions between mpox and FDA-approved drugs. Methods: The primary and secondary structure of the protein was retrieved and FDA approved drug was screened using AutoDock. The best hit was analyzed and the molecular interactions were studied. Model validation analyzes the peptide, energy of hydrogen bonds, steric conflicts and bond planarity. Z-score was calculated using ProSA-web tool and the score tested the native fold from other alternative folds. Results: The confidence level of the submitted amino acids was> 80 % and the maximum confidence score for a single template was 98.2 %. The generated proteinase model was subjected to analyze the distribution of atoms and the using ERRAT server. The overall quality score was 88.535 and this value represents the amino acid percentage with anticipated error value and the value falling below the rejection limit. The Z-score of this study result was within the Z-score range (−4.17) validated for native enzymes. The binding pockets of the enzyme were determined in this study and two binding pockets were predicted using the automatic online tool using the web server. The selected FDA-approved drugs were ordered based on their minimum binding energy to the proteinase. Conclusions: Molecular docking studies revealed the involvement of various hydrophobic interactions between FDA-approved drugs and amino acid residues of monkeypox virus proteinase.